Perivascular epithelioid cell tumor in the mediastinum: Metastasis or multiple primaries? - Jacob C. Kinskey; Mary R. Schwartz; Charles C. Guo; Jae Y. Ro (Human Pathology Reports, 2022)
We report a 38-year-old female with a history of primary pelvic PEComa and subsequent metastatic PEComa to the mediastinum who presented with recurrent mediastinal metastasis in April 2021. At initial presentation in 2010, the patient reported a three-month history of abdominal pain, hot flashes, night sweats, and a one-day history of bloating. Surgery revealed an 18-cm multilobulated pelvic mass involving the posterior uterus, bladder, and bilateral adnexa. Histology showed spindled and epithelioid tumor cells immunopositive for HMB-45, desmin, TFE3, SMA, caldesmon, Melan-A and calretinin. Cytokeratin, S-100, inhibin, myogenin, and OCT3/4 immunostains were negative. In 2013 the patient re-presented with chest pain. Imaging confirmed a mediastinal mass involving the pericardium with histology resembling the previous pelvic mass. Following initial resection and mTOR therapy, the mediastinal mass recurred once in 2015 with similar histologic findings. This case provides the first description of a malignant pelvic PEComa metastasizing to the mediastinum, and demonstrates the challenges associated with diagnosing metastatic PEComa. Though malignant PEComa with metastasis to the mediastinum is rare, it is important to recognize the natural process of this tumor to ensure adequate follow-up and patient care.